Examining the role of lecturer servant leadership in fostering post-millennial student engagement and its impact on learning outcomes - Amruloh, Dedeng Abdul Gani; Saleh, Reza; Ramadittya, Muhammad; Bakar, Zainudin Bin Abu (Indonesian Institute for Counseling, Education and Therapy (IICET), 2025)
The post-millennial generation’s reliance on digital learning tools, compounded by the COVID-19 pandemic, has created an urgent need to redefine pedagogical leadership in higher education. This study fills a critical gap in the literature by empirically testing how servant leadership directly impacts student engagement and learning outcomes. Using a cross-sectional quantitative design data were collected via Likert-scale questionnaires from 100 undergraduate students purposively sampled from private universities with suboptimal e-learning infrastructure. Structural equation modeling (SEM) in AMOS 22 revealed that servant leadership strongly predicts student engagement with an estimated value (λ = 0.911, p <0.001), the influence of Lecturer Servant Leadership on student learning outcomes is significant with a value (λ = 0.609, p = 0.020) and the influence of student engagement on student learning outcomes is small but has a significant impact with a value (λ = 0.160, p <0.001). From the calculation results obtained, the indirect effect of Lecturer Servant Leadership on learning outcomes is 0.146 or 14.6% mediation effect, which means Total Effect = Direct Effect (0.609) + Indirect Effect (0.146) = 0.755, with Proportion of mediation = 0.146 / 0.755 ≈ 19.3%. The results prove that by encouraging “engagement” as cognitive participation, emotional investment, and behavioral interaction, student learning outcomes will increase by lecturer servant leadership model.